Odpowiedzi

2010-03-21T13:44:36+01:00
A) 6x-12=3x+3a
6x-3x=3a+12
3x=3a+12 /:3
x=a+4


b)5y-(-8c+y)=12ab
5y+8c+y=12ab
5y+y=12ab-8c
6y=12ab-8c /:6
y=2ab-8/6c

c)-13z+2(5z-2a)=-20a+5z+40
-13z+10z-4a=-20a+5z+40
-13z+10z-5z=-20a+40+4a
-7z=-16a+40 /:(-7)
z=16/7a-40/7
1 5 1
2010-03-21T13:50:18+01:00
6x-12=3x+3a
6x-3x=3a+12
3x=12+3a /:3
x=4+a

5y-(-8c+y)=12ab
5y+8c-y=12ab
5y-y=12ab+8c
4y=12ab+8c /:4
y=3ab+2c

-13z+2(5z-2a)=-20a+5z+40
-13z+10z-4a=-20a+5z+40
-3z-5z=-20a+4a+40
-8z=-16a+40 /:8
-z=-2a+5 /:(-1)
z=2a-5

1 5 1